We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website.
Please click on "Accept cookies" if you agree to the setting of cookies. Cookies that do not require consent remain unaffected by this, see
cookie policy and privacy policy.
DECLINE COOKIES

What are the coefficients in the expansion of the following expression at x=0: (1 + x)^(-2) and how are they calculated?

Thank you for help.

Guest Oct 16, 2018

edited by
Guest
Oct 16, 2018

#1**+1 **

The most straightforward way to do this is to just do the division.

It's hard to show the process of long division on here.

\(\dfrac{1}{(1+x)^2}=\dfrac{1}{1+2x+x^2}\)

and just set this up as a usual long division, if you go through it a few steps you'll see it's

\(\dfrac{1}{1+2x+x^2} = 1 - 2x + 3x^2 - 4x^3 + 5x^4 \dots + (-1)^k (k+1)x^k,~\forall k \geq 0\)

hrm.. there might be another way to approach it that's pretty straightforward

\(\sum \limits_{k=0}^\infty ~x^k = \dfrac{1}{1-x}\)

\(\dfrac{1}{1+x}=\dfrac{1}{1-(-x)}\)

\(\dfrac{1}{1-(-x)} = \sum \limits_{k=0}^\infty ~(-1)^k x^k\)

\(\dfrac{d}{dx}~\dfrac{1}{1+x} = - \dfrac{1}{(1+x)^2}\)

\(\dfrac{1}{(1+x)^2} = -\dfrac{d}{dx} \left(\sum \limits_{k=0}^\infty~(-1)^k x^k\right) = \\ -\left(\sum \limits_{k=1}^\infty~(-1)^k k x^{k-1}\right) = \sum \limits_{k=0}^\infty~(-1)^k(k+1)x^k\)

.Rom Oct 16, 2018